UNCAN.eu: toward a European federated cancer research data hub - Boutros, Michael; Baumann, Michael; Bigas, Anna; Chaabane, Linda; Guérin, Julien; Habermann, Jens K.; Jobard, Aurélien; Pelicci, Pier Giuseppe; Stegle, Oliver; Tonon, Giovanni; Valencia, Alfonso; Winkler, Eva C.; et al. (Cancer discovery, 2024)
To enable a collective effort that generates a new level of UNderstanding CANcer (UNCAN.eu) [Cancer Discov (2022) 12 (11): OF1], the European Union supports the creation of a sustainable platform that connects cancer research across Member States. A workshop hosted in Heidelberg gathered European cancer experts to identify ongoing initiatives that may contribute to building this platform and discuss the governance and long-term evolution of a European Federated Cancer Data Hub.
Gesehen am 29.11.2024